(untitled) (Brazilian Journal of Pharmaceutical Sciences, 2010)
New Product Portfolio Management is aimed at helping decision-makers better select projects for new products based on key criteria for the manufacturer. The Brazilian pharmaceutical industry has been undergoing change due to stricter sanitary requirements following the enactment of the Generic Law in 1999. This paper presents the results of a research study aimed at clarifying the rationale employed by national pharmaceutical companies in selecting and prioritizing their new product development projects. Consequently, proposals for an analytical structure that could help these companies better select their products were produced. The research was carried out using case study methodology in which four different companies were investigated. The results of the field study confirmed that these companies had a non-structured Product Development System and that the selection of new product development projects was made on a non-systematic basis. The research also identified key criteria for the selection of projects of new pharmaceutical products, which provided the basis for the preparation of a proposal for a managerial standard for application of New Product Portfolio Management.